The Future of Poison Pills in Canada: Are Takeover Bid Reforms Needed? - Anand, Anita (McGill Law Journal / Revue de droit de McGill, 2015)
The rules regarding shareholder rights plans, also known as “poison pills”, ensure that boards of directors facing a hostile takeover bid can retain a poison pill for a period of time in order to search for other potential offers. Over the years, the period of time has grown in length from twenty to thirty-five days and the Canadian Securities Administrators (CSA) have recently proposed a 120-day period during which takeover bids would remain open. In light of the historical rationale of takeover bid law to protect the interests of target shareholders, this article argues that the legal regime should not allow an extensive bid period of 120 days. While other aspects of the CSA proposal are sound, a lengthy bid period disadvantages both target shareholders and bidders and will ultimately deter bids from occurring.